New advances in gastrointestinal motility research - Pullan, A. J.; Farrugia, G.; Cheng, L. K. (Lecture Notes in Computational Vision and Biomechanics, 2013)
Research into gastrointestinal motility has received renewed interest in part due to recent advances in the techniques for measuring the structure and function of gastrointestinal cells, tissue and organs. The integration of this wealth of data into biophysically based computation models can aid in interpretation of experimental and clinical measurements and the refinement of measurement techniques. The contents of this book span multiple scales - from cell, tissue, organ, to whole body and is divided into four broad sections covering: i) gastrointestinal cellular activity and tissue structure; (ii) techniques for measuring, analyzing and visualizing high-resolution extra-cellular recordings; (iii) methods for sensing gastroelectrical activity using non-invasive bio-electro-magnetic fields and for modulating the underlying gastric electrical activity, and finally; (iv) methods for assessing manometric and videographic motility patterns and the application of these data for predicting the flow and mixing behavior of luminal contents by using computational fluid dynamic techniques. This book aims to provide both an overview of historical and existing research techniques as well as to highlight future directions and challenges for the community as a whole. It  will be suitable for clinicians to  understand the cellular and  biophysical underpinnings of gastric emptying, gastroenterologists, surgeons, bioengineers and all scientists with interests in gastrointestinal motility research.